(untitled) (Acta Scientiarum. Agronomy, 2019)
Environment and storage time influence stored seed quality, especially for oilseeds such as castor beans because they have a high lipid content and are more prone to deterioration. This study evaluated the physiological quality of seeds from three castor bean genotypes stored at 10 and 20°C for 300 days. The experimental design was completely randomized, with 4 replications, in a 2 x 6 (2 temperatures x 6 storage periods) split-plot design. The seeds were placed in low-density polypropylene bags and stored in climatic chambers at 10 and 20°C, in which the temperature and relative humidity were registered. Physiological quality (germination, germination rate index, emergence, rate of emergence, electrical conductivity and accelerated aging) were evaluated at baseline and after 60, 120, 180, 240, and 300 days of storage. Castor seeds of genotype EVF 106 showed better physiological quality when stored at 10°C. Castor seeds of genotype EVF 701 could be stored at 10 and 20°C for 300 days. Castor seeds of genotype EVF 712 presented reduced physiological quality during their 300 days in storage, regardless of temperature.